Scattering Amplitudes and Wilson Loops in Twistor Space - Bullimore, Mathew Richard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Scattering amplitudes are fundamental and rich observables in quantum field theory. Based on the observation that, for massless particles of spin-one or more, scattering amplitudes are much simpler than expected from traditional Feynman diagram techniques, the broad aim of this work is to understand and exploit this hidden structure. It uses methods from twistor theory to provide new insights into the correspondence between scattering amplitudes in supersymmetric Yang-Mills theory and null polygonal Wilson loops. By additionally exploiting the symmetries of the problem, the author succeeds in developing new ways of computing scattering amplitudes.
Introduction -- Review -- Amplitudes and MHV Diagrams -- On-Shell Recursion -- Wilson Loops -- Anomalies -- Bibliography.
Keywords: Physics; Quantum theory; Physics; Quantum Field Theories, String Theory; Mathematical Physics; Elementary Particles, Quantum Field Theory; Mathematical Applications in the Physical Sciences